THE CHAT BOX REVELATION ON THE CHAT LANGUAGE OF FLEMISH ADOLESCENTS AND YOUNG ADULTS - Magis, Ester (European Scientific Journal, ESJ, 2013)
In his article ‘Tussentaal wordt omgangstaal in Vlaanderen’, De Caluwe (2009) states that interlanguage is becoming the common colloquial speech in Flanders. He uses the four features put forward by Lemahieu (2008) as his main arguments. Although Lemahieu focused on spoken Standard Dutch, these features can also be used for research of written interlanguage. This contribution examines chat language of 60 subjects, both male and female, within the five Flemish provinces (West Flanders, East Flanders, Antwerp, Flemish Brabant with Brussels and Limburg). Next to gender and geographical divisions age is also taken into account. The research is based upon several online chat conversations that were fragmented and analysed. The analysis of the above-mentioned variants per participant, age and province gives an idea of the presence of interlanguage. The variants of Lemahieu are therefore an interesting tool because they provide data regarding how many times a representative selection of Flemish chatters with regard to a set of variants choose to use interlanguage in a situation in which they have the choice to use inter- or Standard language. The conclusion resulting from this research reveals that there are indeed regional variants and there is a high percentage of interlanguage, but Standard Dutch still prevails. Therefore, it is claimed that chat language does not impoverish the standard written language, but enriches it and that it rather should be considered as change in progress.